BACTERICIDAL METHOD FOR THE MEASUREMENT IN NORMAL SERUM OF ANTIBODY TO GRAM-NEGATIVE BACTERIA - Landy, Maurice (J Bacteriol, 1962)
Landy, Maurice (National Cancer Institute, Bethesda, Md.), J. Gabriel Michael, and James L. Whitby. Bactericidal method for the measurement in normal serum of antibody to gram-negative bacteria. J. Bacteriol. 83:631–640. 1962.—The bactericidal effect of normal serum on gram-negative bacteria was investigated with the objective of determining whether this antibody-complement reaction could be used for the measurement of antibody. The major variables affecting the outcome of this complement-dependent reaction were explored systematically to establish the test conditions in which specific antibody was the limiting factor. Among these were the use of an excess of absorbed human serum as a complement source, inoculum, reaction conditions, and precise enumeration of surviving bacteria. It was demonstrated that the test conditions could be controlled so as to provide a sensitive and objective assay for antibody to representative strains of various gram-negative genera.